Peran Pemerintah Daerah dalam Pengembangan Desa Wisata Paksebali di Kabupaten Klungkung - Putu Sukma Wahyuni Dewi; Luh Nyoman Tri Lilasari; I Gede Gian Saputra (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2021)
This research aims to study the role of local government in the development of Paksebali Tourism Village, from the perspective of local community, tourism village team, and the Klungkung District Government. Data were collected by observation, survey, interviews, documentation and analyzed using qualitative descriptive analysis techniques. The results showed that local people and tourism village team strongly agreed with the government's Paksebali Tourism Village development programe. As a facilitator the government facilitated tourism programs, projects and activities, provided innovations, involved the community to participate, socialization and financial assistance. As evaluators, the government assessed the programs, monitored tourism development and made  satisfaction surveys, as implementers, the government leaded and coordinated programs, projects and activities for the development of tourist villages, established good relationships with relevant agencies and regulated tourism development such as making environmental sustainability, health and safety standards. Of the four roles, the role of the government as facilitator obtained the highest score of 4.35, and as the evaluator obtained the lowest score of 4.21. To maximize the role of the government,  this study recommended the government conduct monitoring and evaluation on the development of Paksebali Tourism Village at least once a month by involving the community and leaders.